Étude et simulation d'un filtre actif parallèle à quatre fils de puissance - LOUETRI, Mohammed; YAMANI, Othman; SMAILI Moulay, Souleyman (University of El-Oued, 2022)
"Recently, the use of power electronic loads is increased. These power electronic loads absorb non-sinusoidal current from the electrical network and behave as harmonic currents generator, which can cause undesirable effects on electrical equipments. This works is a contribution of improving the quality of electric current in such net works. Four wires shunt active filter is studied , deferent topologies with deferent loads (balanced and un balanced ) are discussed .The control is made at the base of High pass filter, which proved very good filtering performance ,either in transient or steady. The structure of a four-wires shunt active power filter and its control strategy are the most important elements in the compensation process. In this work, tow-levels voltage source inverter topology is selected. However, instantaneous active and reactive power theory (p-q) is applied to calculate and identify harmonic currents. The hysteresis controller is used in current control loops. However, the simulations has been performed using Matlab/Simulink . The shunt active filter based on the proposed control strategy has shown good performance in reducing the total harmonic distortion (THDi) of the source current to less than 5% satisfying the international recommendation " "الملخص في السنوات الأخيرة , يعتبر استعمال المحولات الثابتة في تزايد كبير ,حيث أن هؤلاء المحولات يمتصون تيارات غير جيبيه من الشبكة الكهربائية . إذا أنهم يسلكون سلوك مولدات التيار التوافقي الذي يحدث خلل على مستوى الأجهزة الكهربائية. تمثل هذه المورقة مساهمة في تحسين نوعية التيار الكهربائي في مثل هته الشبكات .ندرس المصفي الفعال ذو أربعة خيوط ونستعمل عدة أشكال لهذا المصفي ومختلف أنواع الحمولات )متوازنة وغير متوازنة( .يتم الكشف عن التيار الملوث باستعمال مصفي عالي العبور، وقد أعطى هذا الأخير نتائج ممتازة ، سواء في الحالة العابرة أو السكونية بعد التذكير بأهم الاضطرابات التي تؤثر على الشبكة الكهربائية أسبابها و تأثيرها و مختلف الحلول لتصفية الشبكة من الشوائب . سوف نقوم بدراسة إجمالية لبنية المرشح الفعال المتوازن ذو أربعة أسلاك للاستطاعة , و بعد ذلك نقوم بدراسة تحكم المرشح الفعال القائم على العاكس والطرق المستعملة لتحديد التيارات التوافقية المرجعية وفي هذه الدراسة سوف نستعمل طريقة الاستطاعة اللحظية p-q. و بعد ذالك سوف نتحقق من النتائج عن طريق المحاكاة باستعمال برنامج الماتلاب . النتائج المتحصل عليها تثبت أن المرشح الفعال يتيح لنا الحصول على نتائج جيدة جيدا ,مع أقل من %5 و ذلك ما يوافق القوانين و النظم الدولية ."
مذكرة ماسترتخصص تحكم كهربائي
Keywords: " non-linear lead , Harmonic current , extraction the current harmonics , Total harmonic distortion THD, shunt active power filter four-wires, inverter, method (p-q), "; " الحمولة الغير خطية , التيارات التوافقية ,تحديد التوافقيات للتيارات , معامل تشويه التيار , المرشح الفعال المتوازن ذو أربعة خيوط ,المرشح , طريقة p-q . "